Developing an Educational Package to Improve Attitude of Medical Students Toward People With Mental Illness: A Delphi Expert Panel, Based on a Scoping Review - Rezvanifar, Farahnaz; Shariat, Seyed Vahid; Shalbafan, Mohammadreza; Salehian, Razieh; Rasoulian, Maryam (Frontiers in Psychiatry, 2022)
Introduction: The importance of stigma toward patients with mental illness in medical students as future physicians cannot be overemphasized. There is currently no formal training to reduce stigma toward mental illness in medical students in their educational curriculums in Iran like most other low and middle income countries. Therefore, aiming to provide a practical and effective training package focused on reducing stigma toward patients with mental illness in medical students, the current study conducted, as an expert panel with Delphi method, based on a scoping review, to develop an education package to improve attitude of medical students toward patients with mental illness. Materials and Methods: We surveyed the available international databases including PubMed, Google Scholar, Scopus, PsycINFO, Tripdatabase, Web of Science, Cochrane Database of Systematic Reviews as well as Persian databases including Iranmedex, SID, Irandoc and Magiran in February and March 2020. After an extensive review of related resources, 13 articles met our inclusion criteria. Then, we extracted the related data including type and duration of the interventions, sample size, mean and standard deviation of stigma scores before and after interventions. To develop the package among the included interventions, we asked 16 experts in psychology, psychiatry, and social medicine to rate the interventions based on a number of variables such as effectiveness, feasibility and applicability in a Delphi process. Results: The selected intervention in Delphi method with consensus of experts included a set of four sequential interactive interventions: showing a movie and discussing it, psychiatric training including contact with people who affected psychiatric disorders, social communication with people who affected psychiatric disorders, and group discussion on defining stigma and personal experiences. Conclusion: In the present study, we recommend a set of interventions to reduce stigma toward patients with mental illness among medical students in the form of a package of combined, interactive and sequential interventions that have been previously been shown to be effective in reducing stigma related to mental illness. We expect that implementation of these interventions would reduce mental illness stigma in medical students; which needs further verification.